2022
DOI: 10.3390/microorganisms10040783
|View full text |Cite
|
Sign up to set email alerts
|

A Biomimetic Porcine Urothelial Model for Assessing Escherichia coli Pathogenicity

Abstract: Urinary tract infections can be severe, sometimes fatal, diseases whose etiological pathogens are predominantly uropathogenic strains of E. coli (UPEC). To investigate the UPEC pathogenesis, several models have already been established with minor or major disadvantages. The aim was to develop a simple, fast, and inexpensive biomimetic in vitro model based on normal porcine urothelial (NPU) cells that are genetically and physiologically similar to human bladder urothelium and to perform basic studies of E. coli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 88 publications
1
2
0
Order By: Relevance
“…We have found that more glycocalyx is present in these vesicles when UCs are not terminally differentiated, which is usually the case when UCs are grown in vitro (see Fig. 1C, F, K in the reference (Predojević et al 2022 ).…”
Section: Summary and Open Questionssupporting
confidence: 55%
“…We have found that more glycocalyx is present in these vesicles when UCs are not terminally differentiated, which is usually the case when UCs are grown in vitro (see Fig. 1C, F, K in the reference (Predojević et al 2022 ).…”
Section: Summary and Open Questionssupporting
confidence: 55%
“…In this study, we first examined spontaneously formed TNTs in monocultures (homocellular TNTs) of normal porcine urothelial (NPU) cells and invasive urothelial cancer T24 cells. The NPU cell model corresponded to normal human urothelial cells due to the structural and functional compatibility of porcine-derived NPU cells with normal human urothelial cells ( Visnjar et al, 2012 ; Resnik et al, 2015 ; Višnjar and Kreft, 2015 ; Resnik et al, 2018 ; Predojevic et al, 2022 ). Next, TNTs were studied in cocultures (heterocellular TNTs) of NPU and T24 cells to simulate intercellular communication in cancer tissues.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a multilayered biomimetic porcine urothelial model that has been shown to react differently to pathogenic vs. non-pathogenic E. coli strains has been used for evaluating the antimicrobial properties of PnDs ( Ramuta T.Ž. et al, 2021 ; Predojević et al, 2022 ). Similar complex in vitro models have been established to study the host-pathogen interactions in the airway mucosa ( Marrazzo et al, 2016 ; Hasan et al, 2018 ), intestine ( Pearce et al, 2018 ; García-Díaz et al, 2022 ) and skin ( Bolle et al, 2020 ), but have not yet been used for evaluation of PnDs.…”
Section: Antimicrobial Effects Of Perinatal Derivativesmentioning
confidence: 99%